Nanocarrier-Based Drug Delivery Systems Targeting Kidney Diseases - Laura Zucaro; Consiglia Longobardi; Antonio Miele; Antonio Villanova; Yoko Suzumoto (Karger Publishers, 2024)
Background: The potential applications of nanotechnology in the medical field have become increasingly recognized in recent years. Nanocarriers have emerged as a versatile tool, offering a wide range of applications due to their unique properties. In addition to the targeted drugs delivery, nanocarriers have also proven to be extremely effective in imaging and diagnostics. Continuous advances in nanotechnology have paved the way for innovative solutions to complex challenges in human health, shaping the future of nanotechnology and its applications. Summary: By exploring different types of nanoparticles, this review delves into the different characteristics that can be tailored to enhance their kidney access. Although the structural complexity of the kidney may prevent nanocarriers passage, optimization of nanocarrier characteristics such as shape, size, charge, and surface modifications may overcome these barriers, allowing for targeted delivery. By harnessing the potential of nanoparticles, researchers aim to develop targeted and efficient therapies that can address various kidney-related disorders. Key Messages: This review highlights the promising advancements in nanotechnology and their potential impact on improving the therapeutic outcomes for several kidney diseases.